2016
DOI: 10.1128/genomea.01428-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Mosaic NADC30-Like Porcine Reproductive and Respiratory Syndrome Virus in China

Abstract: Here, we report the complete genome of an NADC30-like porcine reproductive and respiratory syndrome virus (PRRSV) strain, HNhx, which was isolated from Henan Province, China, in 2016 and was characterized by recombination with JXA1 strain (an epidemic highly pathogenic PRRSV strain in China) in Nsp4 to Nsp9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The dramatic increase in the recombination rate since 2015 may be attributable to the wide spread of NADC30-like strains (Figure 2; Yu et al, 2012;Sui et al, 2018;Zhou et al, 2018a,c;. It was difficult to identify the characteristic regions of recombination in the PRRSV genome in this research and other studies (Yuan et al, 1999;Wang L. J. et al, 2016;Liu et al, 2017;Zhou et al, 2018b,c;Zhang W. L. et al, 2019). Evidences showed that recombination can changefv PRRSV virulence.…”
Section: Discussionmentioning
confidence: 71%
“…The dramatic increase in the recombination rate since 2015 may be attributable to the wide spread of NADC30-like strains (Figure 2; Yu et al, 2012;Sui et al, 2018;Zhou et al, 2018a,c;. It was difficult to identify the characteristic regions of recombination in the PRRSV genome in this research and other studies (Yuan et al, 1999;Wang L. J. et al, 2016;Liu et al, 2017;Zhou et al, 2018b,c;Zhang W. L. et al, 2019). Evidences showed that recombination can changefv PRRSV virulence.…”
Section: Discussionmentioning
confidence: 71%
“…First, the complete genome sequences of NADC30‐like PRRSV strains show high genetic diversity and their homology is approximately 86%–97.1% (Liu et al., ), which is far below that of HP‐PRRSVs (over 99%). Second, recombination is widely visible, which generates many mosaic viruses between the NADC30 virus and the classic PRRSV, HP‐PRRSV or both (Li et al., ; Wang, Guo, Qiao, Chen, & Zhang, ). Third, the pathogenicity in piglets is diverse between the different strains, although most show moderate virulence (Bian et al., ; Sun et al., ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The recombination of PRRSV was first confirmed in the laboratory using two different PRRSV strains to co-infect MA-104 cells [ 149 ]. Since then, numerous field isolates with the characterization of recombination among field strains and MLVs have been recognized [ 150 , 151 , 152 , 153 , 154 ]. Based on our continual monitoring on field isolates and recombination analyses on all available whole genomic sequence of Chinese PRRSV-2 in the GenBank database, we found that during the year 2012 to 2017, the ratio of recombined virus significantly increased year by year, which is consistent with the results currently published by Jiang et al [ 121 ].…”
Section: Concerns About MLV Safetymentioning
confidence: 99%